2016
DOI: 10.1007/s11274-016-2097-1
|View full text |Cite
|
Sign up to set email alerts
|

Cold stress promoting a psychrotolerant bacterium Pseudomonas fragi P121 producing trehaloase

Abstract: A newly isolated Pseudomonas fragi P121 strain in a soil sample taken from the Arctic Circle is able to produce trehalose. The P121 strain was able to grow at temperatures ranging from 4 to 25 °C, had an optimum pH of 6.5, and an optimum salt concentration of 2 %. The P121 strain had a survival rate of 29.1 % after being repeatedly frozen and thawed five times, and a survival rate of 78.9 % when placed in physiological saline for 15 days at 20 °C after cold shock, which is far higher than the type strain Pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Pseudomonas spp. are regarded as psychrotolerant and broad-host-range entomopathogenic bacteria exhibiting insecticidal activity toward certain agricultural pests (Chen et al, 2014;Mei et al, 2016). It appears that these bacteria and fungi might be involved in the blastospore-mycelium transition during larval mummification process.…”
Section: Mummification-related Bacteria and Fungimentioning
confidence: 99%
“…Pseudomonas spp. are regarded as psychrotolerant and broad-host-range entomopathogenic bacteria exhibiting insecticidal activity toward certain agricultural pests (Chen et al, 2014;Mei et al, 2016). It appears that these bacteria and fungi might be involved in the blastospore-mycelium transition during larval mummification process.…”
Section: Mummification-related Bacteria and Fungimentioning
confidence: 99%
“…Certain bacterial and fungal species produce this compound under freezing conditions (Ohtake & Wang, 2011). Trehalose provides a protective effect and minimizes cell lysis (Mei et al, 2016). P121 also has the ability to provide protection to its cells by detoxifying harmful substances and using aromatic compounds as carbon and nitrogen sources, which is beneficial in surviving very low temperatures (Yanzhen, Yang, Xiangting, & Wei, 2016).…”
Section: Strain Diversitymentioning
confidence: 99%
“…The bacterial strain P121, identified as P. fragi , is an isolate from Arctic Ocean coast soil where the average temperature is below 10 °C. It is a marine bacterium that can grow between 4 and 25 °C in culture medium with added sea salt (Mei, Huang, Liu, He, & Fang, ). Studies have found that the survival rate of the P121 strain was far higher than the survival rate of the P. fragi type strain ATCC 4973 after the same cold shock exposure.…”
Section: Pseudomonas Fragimentioning
confidence: 99%
“…In addition to improving photosynthetic capacity and, thus, yield and biomass production, these symbiosis influence carbohydrate metabolism (e.g., trehalose biosynthesis in Pseudomonasfragi P121 (Table 2), Leucosporidium fellii (Table 1), and Mrakia frigida (Table 3), trehalose and glycerol biosynthesis in Saccharomyces cerevisiae, and upregulation of malate dehydrogenase in Rhizobium), which play a crucial role in cold acclimation (Sardesai and Babu 2001;Panadero et al 2006;Maggi et al 2013;Mei et al 2016). The production of unsaturated membrane lipids to maintain membrane fluidity, RNA chaperons to suppress the formation of undesired secondary RNA structures, the synthesis of antifreeze and cold shock proteins, as well as cold-active antioxidant enzymatic and non-enzymatic activities may also have a prominent role in microbiome cold acclimation (Maggi et al 2013;Ghobakhlou et al 2013).…”
Section: Plant-bacteria and Plant-yeast Symbiosis Under Low Temperaturesmentioning
confidence: 99%